Methodologies, perspectives and strategies to promote holistic assessment of health and activity behaviours in youth with developmental disabilities: a narrative review - Vincenzo G Nocera; Angela J Wozencroft; Dawn P Coe (BMJ Open Sport & Exercise Medicine)
Physical activity is known to have multiple health benefits for youth with developmental disabilities (DDs). Individuals with DDs are at risk for adverse health-related outcomes. Limited research has shown that the prevalence of youth meeting recommendations for physical activity is low. However, there are challenges in assessing physical activity and achieving adequate compliance in this population, which may lead to inaccurate data. Factors that play a role in the ability of an individual to participate in adequate physical activity to meet recommendations include the ability to perform motor skills and the functional capacity to pursue and engage in a variety of activities. The purpose of this narrative review is to describe the current practices, barriers and strategies associated with physical activity, motor proficiency and metabolic assessments in youth with DDs. This paper elucidates barriers to physical activity, motor proficiency and metabolic assessments in youth with DDs while providing strategies to aid in the successful administration of protocols. Evidence-based and anecdotal evidence provided in this paper supports the use of the following strategies to aid in assessment: peer modelling, parent support, individualised behaviour techniques, positive reinforcement and the use of social narratives. Future work in this area should continue to (a) critically evaluate, implement and develop assessment tools and protocols in youth with DDs and (b) establish reference data specific to the target population.